Penggunaan Surat Kuasa Membebankan Fidusia (SKMF) Di Bawah Tangan sebagai Dasar Pembuatan Akta Fidusia Ditinjau Dari Hukum Jaminan Di Indonesia - Mohamad Toha Dhukas (Universitas Islam Indonesia, 2016)
AbstractProblems in this study, the first: whether the use SKMF under the hand as the basis for loading / fiduciary deed can be done, if the terms of the legal guarantee? Second, how is the legal effect of the fiduciary certificates have been obtained creditor, if at the time of loading / deed fidusianya, fueled by SKMF under the hand? The research is a normative juridical. The study concluded that, first, the use of SKMF under the hand as the basis for loading / fiduciary deed can not be justified under the national security law. Although UUJF not set, this does not mean the use of SKMF under the hand can be justified. Second, with the use of a power in the loading / fiduciary deed, then the validity of the result obtained from the loading / fiduciary deed, will depend (dependent) on the validity of proxies. So if creditors overburden / a deed of fiduciary through SKMF under the hand, it will bring consequences can not be obtained privileges as promised by law to creditors fiduciary certificate holder.Keywords: power of attorney, deeds, fiduciary guarantees.